2014
DOI: 10.1007/s11745-014-3918-3
|View full text |Cite
|
Sign up to set email alerts
|

Fast Transmethylation of Total Lipids in Dried Blood by Microwave Irradiation and its Application to a Population Study

Abstract: A methodology combining finger-pricked blood sampling, microwave accelerated fatty acid assay, fast gas chromatography data acquisition, and automated data processing was developed, evaluated and applied to a population study. Finger-pricked blood was collected on filter paper previously impregnated with 0.05 mg of the antioxidant butylated hydroxytoluene and air-dried at room temperature. Transmethylation was accelerated by microwave irradiation in an explosion-proof multimode microwave reaction system. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 37 publications
0
14
1
Order By: Relevance
“…Contrary to our findings with sphingomyelin, at least three previous studies have shown a reduced yield for very-long chain SFA and MUFA with the use of microwave-assisted transesterification both in serum/plasma and whole blood [1,6,16]. Most recently, two studies from one research group using a similar but multi-modal microwave system from the same company found yields of 70-90 % for 20:0, 22:0, 24:0 and 24:1n-9 [6] and 20-70 % for the same fatty acids in an earlier study [16].…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Contrary to our findings with sphingomyelin, at least three previous studies have shown a reduced yield for very-long chain SFA and MUFA with the use of microwave-assisted transesterification both in serum/plasma and whole blood [1,6,16]. Most recently, two studies from one research group using a similar but multi-modal microwave system from the same company found yields of 70-90 % for 20:0, 22:0, 24:0 and 24:1n-9 [6] and 20-70 % for the same fatty acids in an earlier study [16].…”
Section: Discussioncontrasting
confidence: 99%
“…Most recently, two studies from one research group using a similar but multi-modal microwave system from the same company found yields of 70-90 % for 20:0, 22:0, 24:0 and 24:1n-9 [6] and 20-70 % for the same fatty acids in an earlier study [16]. These two studies employed acetyl chloride in methanol (~11 % by volume) as per the method of Lepage and Roy [27], and contrary to what we show in the present study, increasing the reaction time had no effect on fatty acid yield.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations